Estrogen receptor and laminin genetic polymorphism among women with pelvic organ prolapse - Bothaina Nakad; Fuad Fares; Naiel Azzam; Benjamin Feiner; Ariel Zilberlicht; Yoram Abramov (Elsevier, 2017)
Objective: Laminin is a connective tissue component. The LAMC1 gene encodes for gamma-1 chain of laminin, which is associated with familial clustering of POP. The ERα gene which encodes for cellular estrogen receptor has also been associated with POP. The aim of this study was to evaluate a possible correlation between polymorphism in these genes and the risk for developing POP. Materials and methods: Blood samples were drawn from 33 women with advanced POP (study group) and 33 women without POP (control group). DNA was extracted, and the presence of the rs10911193 C/T mutation in LAMC1 and of the rs2228480 G/A mutation in ERα was detected using the PCR technique. Results: 26 samples were available for each group regarding ERα. 33 samples were available for each group, regarding LAMC1. The prevalence of homozygotes for the ERα rs2228480 G/A mutation was 19.2% and 0% among women with and without POP, respectively (OR 39.77, 95% CI 1.93-817.0, P = 0.00046). The prevalence of heterozygotes for this mutation was 83.3% and 11.5%, respectively (OR 19.2, 95% CI 4.15-88.6, P < 0.0001). The prevalence of homozygotes for the LAMC1 gene rs10911193 C/T mutation was 3.6% and 6.1% among women with and without POP (NS), while the respective for heterozygotes for this mutation was 21.4% and 33.3% (NS). Conclusions: Polymorphism in the ERα gene is associated with an increased risk for advanced POP. However, polymorphism in the LAMC1 gene does not seem to be associated with such risk.